Intraspinal neural stem cell transplantation in amyotrophic lateral sclerosis: Phase 1 trial outcomes. Issue 3 (7th March 2014) - Feldman, Eva L.; Boulis, Nicholas M.; Hur, Junguk; Johe, Karl; Rutkove, Seward B.; Federici, Thais; Polak, Meraida; Bordeau, Jane; Sakowski, Stacey A.; Glass, Jonathan D.
<x xml:space="preserve">Abstract</x> Objective The US Food and Drug Administration–approved trial, "A Phase 1, Open‐Label, First‐in‐Human, Feasibility and Safety Study of Human Spinal Cord‐Derived Neural Stem Cell Transplantation for the Treatment of Amyotrophic Lateral Sclerosis, Protocol Number: NS2008‐1, " is complete. Our overall objective was to assess the safety and feasibility of stem cell transplantation into lumbar and/or cervical spinal cord regions in amyotrophic lateral sclerosis (ALS) subjects. Methods Preliminary results have been reported on the initial trial cohort of 12 ALS subjects. Here, we describe the safety and functional outcome monitoring results for the final trial cohort, consisting of 6 ALS subjects receiving 5 unilateral cervical intraspinal neural stem cell injections. Three of these subjects previously received 10 total bilateral lumbar injections as part of the earlier trial cohort. All injections utilized a novel spinal‐mounted stabilization and injection device to deliver 100, 000 neural stem cells per injection, for a dosing range up to 1.5 million cells. Subject assessments included detailed pre‐ and postsurgical neurological outcome measures. Results The cervical injection procedure was well tolerated and disease progression did not accelerate in any subject, verifying the safety and feasibility of cervical and dual‐targeting approaches. Analyses on outcome data revealed preliminary insight into potential windows of stem cell biological activity and identified clinical assessment measures that closely correlate with ALS Functional Rating Scale‐Revised scores, a standard assessment for ALS clinical trials. Interpretation This is the first report of cervical and dual‐targeted intraspinal transplantation of neural stem cells in ALS subjects. This approach is feasible and well‐tolerated, supporting future trial phases examining therapeutic dosing and efficacy. Ann Neurol 2014;75:363–373